Gérmenes causales y susceptibilidad antimicrobiana en infección urinaria asociada a catéter vesical permanente en mayores de 18 años - Mondragón Flores, Brayan Jerson (2020)
Objective: To identify causative germs and antimicrobial susceptibility in urinary infection associated with permanent bladder catheter in over 18 years in Intensive Care Unit of the Belén Hospital in Trujillo during 2013-2018. Material and Method: Observational, descriptive, cross-sectional study, in which the clinical history of each patient with urinary tract infection associated with permanent bladder catheter was reviewed, causal germs and antimicrobial susceptibility of the isolated germ were identified. Results: The most frequently isolated germs were Pseudomona aeruginosa (40.9%), Klebsiella peumoniae (15.2%), Escherichia coli (15.2%), Klebsiella oxytoca (7.6%), all of which had a high sensitivity to imipenem and a variable resistance with the rest of antibiotics and Candida Tropicalis (4.5%) with a greater sensitivity to fluconazole and voriconazole. Conclusions: Pseudomona aeruginosa, Klebsiella penumoniae, Escherichia coli, Klebsiella oxytoca, Candida tropicalis are the most isolated germs in urinary tract infection associated with permanent bladder catheter, sensitivity to imipenem in Intensive Care Unit is high, and a varied behavior with respect to its antimicrobial resistance.